PENGARUH NAUNGAN TERHADAP PERTUMBUHAN BIBIT GAHARU (Aquilaria malaccensis) DI PERSEMAIAN JURUSAN KEHUTANAN, FAKULTAS PERTANIAN UNIVERSITAS PATTIMURA. - Hayani, Hayani; Sahupala, Andjela; Komul, Yulianus (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
Agarwood (Aquilaria malaccensis) is a non-timber forest product commodity that has a high selling value. Indonesia is the largest agarwood producer in the world. By the end of 1990, Indonesia could produce more than 600 tons of agarwood annually. The research was carried out in the nursery of the Forestry Department, Faculty of Agriculture, Patimura University. This research was carried out from February to May 2024 to determine the effect of shade on the growth of gaharu seedlings (Aquilaria malaccensis). The percentage of shade supports the growth of (Aquilaria malaccensis). The experimental design used was a Completely Randomized Design (CRD) with 4 treatments, namely no shade, 50% shade, 65% shade, and 75% shade. The research results show that gaharu seeds are a semi-tolerant type, or a type of gaharu tree that can grow in open and shaded areas.